Understanding biosynthetic protein–protein interactions. Issue 11 (22nd October 2018) - Ackerley, David F.; Challis, Gregory L.; Cryle, Max J.
Abstract : The Natural Product Reports themed issue on Understanding biosynthetic protein–protein interactions is introduced by the Guest Editors, David Ackerley, Gregory Challis and Max Cryle.